Factores sociodemográficos y capacidad de autocuidado del paciente adulto con hipertención y diábetes - Esquivel Quiñe, Ana María (2017)
The present research study of quantitative type and of descriptive, transversal cut design had the objective of determining the self-care capability in adult diabetic and hypertensive people who attend the Pesqueda III Health Center belonging to MINSA, for the 2014 period. The results got from the poll showed the age groups according to the population´s selfcare. These were in people older than 55 yo, the self-care level was 80%, and in people younger than 36 yo, the self-care level was deficient; women predomi-nating over man in 71% with a good self-care. Applying the statistical test p<0.05, we conclude that there is a very significant be-tween age and self-care level. The population under research stated having only finished High School in 25%, with a good self-care, and with a 20% with a University or College Degree, which shows a good self-care level. That is, a significant correlation exists between edu-cational attainment and self-care, this being p<0,005. Eventually, it was found that the time disease in patients with hypertension and/or diabetes was 8 years or more, with a good self-care level in 40%, and 20% in a deficient way in the disease time, with less than 5 years. In this way, it was found that p<0,005, confirming that it exists a significant relation between the disease time and the self-care capabilities level, allowing, in this way, the existing relation between socio-demographic factors and the self-care capabilities in adult patients with hypertension and/or diabetes.